Interest as a supplementary criterion in the detection of talent: The identification of differing types of children at primary school age - Spies, F.; Heger, L.; Bindel, T.; Pfeiffer, M. (International Journal of Sports Science & Coaching, 2024)
Current efforts to design an effective method of detecting talent are now focused on the differing interests of children (preferences) and not just their sport-related motor skills (ability). When a person-oriented approach is used, it is important to profile different types to design movement offers that effectively target the relevant groups and prevent dropouts. The aim of this study was to investigate in the elementary school context what types it is possible to identify in terms of both interests and ability. A total of 159 children (age 8-11.5) were assessed to determine their interests and their ability using a sequential design approach. `Preferences` were scored on a seven-point Likert scale during a video-assisted interview. `Ability` was assessed using seven sport-related motor skills tests. The mixed-methods approach consisted of a quantitative step 1, a cluster analysis (SPSS27, Ward's method, squared Euclidean distance). Based on the clusters, in-depth qualitative interviews were conducted in step 2. Analysis revealed five clusters of children that exhibited significant differences in terms of ability and interests. The qualitative interviews clarify the characteristics of the types (e.g. special interest in recreational activities or in competing at a high level with high or low own performance) and describe their experiences and desires. The data indicates that children's interests are determined by positive experiences and prior knowledge. Schools, sports practice, and sports science are faced with the task of responding suitably to children with different combinations of ability and preferences in the early phase of talent detection.